Development and Processing of Vegetable Oils for Human Nutrition - Przybylski, Roman (AOCS Press, 2011)
Development and Processing of Vegetable Oils for Human Nutrition provides the reader with up-to-date information about vegetable oils: from nutrition and food industry requirements through genetic modification and seed production to regulatory aspects of new oils and crops. This book is a valuable resource for oilseed processors, producers, breeders, agronomists, crop biochemists, nutritionists, regulatory authorities/agencies, and animal scientists.